Role of Corticosteroid in Reducing Post Operative Complication Following Extraction of Impacted Mandibular Third Molar - Khan, Yahya; Khan Tareen, Mirza; Hussain, Mushahid; Muhammad Ammar; Siddique Ullah; Muhammad Bilal (Indus Journal of Bioscience Research, 2025)
Maxillofacial surgery, one of the most commonly performed surgeries in oral and maxillofacial surgery, was the surgical removal of impacted third molars of the mandible. Although it was routine, it was often linked to postoperative complications (e.g., pain, swelling, trismus, difficulty with mastication, and dry socket) because of the postoperative inflammatory response. The use of corticosteroids has been extensively applied in reducing postoperative morbidity, but its use did not flourish because of a lack of local evidence of its efficacy. This research aimed at establishing the prevalence of postoperative complications among patients who used corticosteroids after the extraction of impacted mandibular third molars. This was a five-month period, cross-sectional and descriptive study in the oral and maxillofacial department of sandeman provincial hospital Quetta during the period from January 2025 to May 2025. Non-probability consecutive sampling was used to select 252 patients aged 18-65 years who had surgical exodontomy of affected third molars of the mandible. Individuals were excluded who had systemic disease, immunocompromised status, renal or liver impairment, coagulopathy, or pregnancy. All operations were done by one experienced operator using a standardized procedure. In the postoperative period, 4 mg IV corticosteroid, standard analgesics, and antibiotics were used for all patients. The complications assessed on postoperative day 1, 3, and 7 were pain (VAS >3), trismus (